Mutagenesis in Escherichia coli by Three O6-Substituted Guanines in Double-Stranded or Gapped Plasmids - Pauly, Gary T; Hughes, Stephen H; Moschel, Robert C (Biochemistry (Easton), 1995)
Plasmids were constructed with guanine (G) or O6-methyl- (m6G), O6-ethyl-(e6G), or O6-benzyl- (b6G) guanine in the initiation codon (ATG) of the lacZ' gene. Four deoxyuridine residues were incorporated near the modified guanine in the complementary strand. The deoxyuridine-containing plasmids exhibited similarly high transformation efficiencies in ung- Escherichia coli, although the frequency of mutations induced by m6G, e6G, and b6G residues was relatively low. Treatment of the plasmids with uracil-DNA glycosylase (UDG), to remove the uracil residues, or UDG and exonuclease III, to create a gap in the deoxyuridine-containing strand, reduced transformation efficiency for adduct-containing plasmids but did not affect transformation efficiency for control plasmids. However, the same treatments dramatically enhanced mutagenesis by m6G, e6G, and b6G. These results were consistent with blockage of replication by the modified guanines in double-stranded plasmids resulting in preferential replication of the complementary strand. Replication past the modified guanines was forced in the gapped plasmids. The frequency of modified guanine-induced mutations in gapped vectors was similar in strains of E. coli that were proficient in DNA polymerase III but deficient in either DNA polymerase I or II or both polymerase I and II suggesting either that polymerase III was primarily responsible for adduct bypass in all strains or that the probability of base misinsertion during bypass by either polymerase I or II was similar to that for polymerase III. Repair studies with gapped plasmids indicated that m6G was subject to repair by Ada methyltransferase and to postreplication processing by methylation-directed mismatch repair. Neither e6G nor b6G were similarly repaired.